2017
DOI: 10.1074/jbc.m116.764324
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Protein S3 Negatively Regulates Unwinding Activity of RecQ-like Helicase 4 through Their Physical Interaction

Abstract: Edited by Patrick SungHuman RecQ-like helicase 4 (RECQL4) plays crucial roles in replication initiation and DNA repair; however, the contextual regulation of its unwinding activity is not fully described. Mutations in RECQL4 have been linked to three diseases including Rothmund-Thomson syndrome, which is characterized by osteoskeletal deformities, photosensitivity, and increased osteosarcoma susceptibility. Understanding regulation of RECQL4 helicase activity by interaction partners will allow deciphering its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
(86 reference statements)
0
21
0
Order By: Relevance
“…The functional domain of rpS3 for DNA repair As rpS3 is involved in DNA repair [13], we have elucidated the exact repair domain of the protein. According to previous studies, the repair domain for endonuclease activity was found to be in the C-terminus region of rpS3 [12,22]. To verify this domain, we constructed several deletion mutants using GST vector (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional domain of rpS3 for DNA repair As rpS3 is involved in DNA repair [13], we have elucidated the exact repair domain of the protein. According to previous studies, the repair domain for endonuclease activity was found to be in the C-terminus region of rpS3 [12,22]. To verify this domain, we constructed several deletion mutants using GST vector (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the repair domain of rpS3 is located at the C terminus [22,23]. However, these studies did not describe the domain in detail, and there are insufficient data on how it works in mammalian cells.…”
mentioning
confidence: 99%
“…Certain r-proteins have been reported as having extra-ribosomal functions relating to various biological processes or functions in mammals (29,30), yeast (31)(32)(33), and bacteria (3,4,34). However, there are some functions of r-proteins unrelated to ribosome function that remain to be determined (2,3,35).…”
Section: Discussionmentioning
confidence: 99%
“…The first reported extra‐ribosomal function of rpS3 was its role as a DNA repair endonuclease that cleaves UV‐damaged DNA strands, 21 and its involvement in various DNA repair processes has been elucidated 19‐22,25,40,41 . However, we had previously found that rpS3 can also act as an apoptotic mediator in some cell lines 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, rpS3 is reported to be involved in the oxidative stress response in mitochondria, helping repair oxidatively damaged mitochondrial DNA 24 . Moreover, rpS3 interacts with the RecQ‐like helicase RECQL4, an important DNA replication and repair helicase, and negatively regulates its helicase activity, possibly to modulate DNA repair processes 25 . Besides these DNA repair‐associated activities, rpS3 also exerts its effect through the NF‐κB complex that is involved in mediating cellular responses to bacterial infection 26‐28 .…”
Section: Introductionmentioning
confidence: 99%